Adolescents At-Risk in the Situation of Transition: Assistance Programs in the Israeli Educational System - Vaxberg, Zivit (Wydawnictwo Naukowe UAM, 2015)
Adolescents at-risk are defined as adolescents who may be found in physical, mental, or emotional situations of risk. Most of them come from dysfunctional families, poverty, or delinquent social environment. Their problems are expressed mainly in the emotional, educational, social and behavioral realms and lead them to absences from school, low educational achievements, behavior problems, and social difficulties. These problems increase dramatically in the phase of transition from middle school to high school. This transition is characterized primarily by: (a) change from a familiar, intimate place to a large, strange, and anonymous place, (b) change of role – from being the oldest pupil to being the youngest one, and (c) separation from significant adults and friends. The Israeli educational system has developed special assistance programs for the transition phase of adolescents at-risk. These programs operate in two parallel and complementary dimensions. During school time, there are special programs such as psychodrama groups which are aimed at strengthening the learners’ perseverance and increasing their success in the normative frameworks. After the school hours, the programs provide them with activities such as mental support and help in their homework preparation.
Młodzież zagrożona w momencie przejścia do szkoły wyższego szczebla – programy pomocowe w izraelskim systemie oświaty
Keywords: adolescents at-risk; transition programs; Israeli educational system